Cation isotopes trace chemical weathering - Long-Fei Gou; Fang Huang; Shouye Yang; Gangjian Wei; Zhi-Qi Zhao; Zhangdong Jin (Fundamental Research, 2025)
Chemical weathering of rocks and minerals alters the geochemical compositions of the lithosphere, hydrosphere, and atmosphere over time, regulating Earth's surface temperature by consuming atmospheric CO2 so as to sustain our habitable planet. As the most mobile species in the processes of chemical weathering, cations are thought to be robust geochemical tracers of chemical weathering. Over the past decades, numerous tracers have been proposed for monitoring chemical weathering, mainly focusing on the contents and ratios of cations. Because of the difference from the properties of cations, information that they provide on chemical weathering over different timescales can be inconsistent or even false, such that some avenues of research have reached an impasse. By virtue of the identical properties of isotopes of the same element and the high-dimensional information that they carry, the stable isotopes of cations have been employed to objectively trace chemical weathering processes, which has become a rapidly developing direction of chemical weathering research. In this review, we summarize the progress made in tracing chemical weathering via the stable cation isotopes (δ7Li, δ26Mg, δ41K, δ44/40Ca, δ87/85Rb, δ88/86Sr, and δ138/134Ba) and point out the development trends and persisting problems. After considering the virtues and deficiencies of various cation isotopes, we recommend the combination of multiple cation isotopes that complement and support one another as the future direction to obtain the reliable information on each process of chemical weathering. This should provide the most effective method for objectively tracing chemical weathering, thereby deepening our understanding of the regulatory mechanisms influencing the habitable surficial temperature.